Bridging the value-action gap: Compliance with Kyoto in the Environmental Liability Directive - Doggen, Nick (Student Undergraduate Research E-journal!, 2016)
This paper analyses compliance with the 2004/35/CE Environmental Liability Directive (ELD) in Sweden, the United Kingdom, Greece and Italy. Their compliance with the ELD reflects in how far pro-environmental ‘actions’ have been taken. Comparing compliance with environmental statements or ‘values’ made in their national parliaments displays to what extent there is a mismatch between values and actions, or a ‘value-action gap’. The four countries each represent one of the Four Worlds of Implementation, a model by Falkner and Treib studying general patterns of compliance with EU Directives. The ELD furthers the polluter-pays principle evident in the Kyoto Protocol. In this regard, the value-action gap helps identifying problem areas in European climate governance.